Prevention of degradation of the natural high potency sweetener (2R, 4R)-monatin in mock beverage solutions. (15th April 2015) - Storkey, Corin; Pattison, David I.; Koehler, Jamie A.; Gaspard, Dan S.; Evans, Jeff C.; Hagestuen, Erik D.; Davies, Michael J.
Highlights: The natural sweetener monatin is degraded on exposure to light and metal ions. Decomposition involves indole ring destruction by radicals and singlet-oxygen. Decomposition is decreased by metal ion chelators, light filters and antioxidants. Monatin degradation can be limited by choice of treatments, additives and container. Abstract: Exposure of the naturally-occurring sweetener monatin to light and metal ions results in loss of both parent monatin and total indole (monatin plus monatin lactone/lactam) in mock beverage solutions, with an accompanying decrease in sweetness. In this study potential protective strategies to prevent degradation were investigated. Metal ion chelating resin, or the chelators EDTA and desferrioxamine decreased monatin and indole loss for solutions kept either in darkness or exposed to light. Tannic acid and Chinese bayberry extract both afforded protection, but this did not arise from a light filtering effect. Plastics with defined absorbance characteristics provided protection with this being wavelength dependent; yellow transparent PET plastic was most effective. The contribution of these interventions (metal ion removal/binding; antioxidant; light absorption) was additive, with combinations providing the greatest protective effect against monatin and indole loss. These results indicate that it is possible to minimise monatin degradation by appropriate choices of treatments, additives and container.